PELAKSANAAN SERTIFIKASI ISO 9000 SEBAGAI ANTESENDEN KEPUASAN PELANGGAN PADA PERUSAHAAN MANUFAKTUR - Respati, Harianto (Jurnal Ekonomi Modernisasi, 2009)
The prevailing free of CAFTA makes South East Asia becoming the new economical area for China. For most manufacturers, it is new opportunity and challenge for them to improve their performances by improving quality of the products and customer satisfaction. Export and import activities among the ASEAN countries and China make the standardized role of ISO 9000 to be most strategic for the manufacturing products. This journal is presented to assist the next researchers who require references about ISO 9000 review and Customer Satisfaction, both theoretically and practically